Existence of Solutions for a Coupled System of Second and Fourth Order Elliptic Equations - Fanglei Wang (Abstract and Applied Analysis)
The generalized quasilinearization technique is applied to obtain a monotone sequence of iterates converging uniformly and quadratically to a solution of a coupled system of second and fourth order elliptic equations.